External Genetic Characteristics and Introgression Rate Bangkok Chicken in Kendari City - Rusli Badaruddin; Muhammad Amrullah Pagala; La Ode Nafiu; Takdir Saili (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2022)
The aim of the study was to identify and analyze external genetic diversity and the introgression rate of bangkok chickens in the city. This research was carried out from November to December 2022 in Kendari City. The materials used in this study were 400 bangkok chickens, consisting of 200 males and 200 tails with an age range of 6 months to 2 years. The variables observed in this study were qualitative traits which included coat color, comb shape and shank color, and introgression rate. The results of the study of the highest controlling gene frequency for external characteristics in Bangkok chickens in Kendari City were colored feather color (ii) (100%), wild feather pattern (e+_) (33,50%), golden glitter (ss) (66,50%) plain coat pattern (bb) (72,75%), white shank color (idid) (55%) and pea comb shape (P_) (99,25%). The value of influence (introgression) from Europeans and Americans on Bangkok chicken in this study was very high, namely 58,65% with an authenticity level of 49,25%. Based on the average heterozygosity value, Bangkok chicken is relatively high with an average expected heterozygosity value of 36,95% per individual.